2006
DOI: 10.1002/joc.1406
|View full text |Cite
|
Sign up to set email alerts
|

An Arctic and antarctic perspective on recent climate change

Abstract: Abstract:We contrast recent climatic and environmental changes and their causes in the Arctic and the Antarctic. There are continuing increases in surface temperatures, losses of sea ice and tundra, and warming of permafrost over broad areas of the Arctic, while most of the major increase in Antarctic temperatures is on the Antarctic Peninsula associated with sea ice loss in the Bellingshausen-Amundsen Seas sector. While both natural atmospheric and oceanic variability, and changes in external forcing includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(100 citation statements)
references
References 62 publications
3
92
0
2
Order By: Relevance
“…The ice area study across East Antarctica (10°W to 172°E) revealed a statistically significant increase of 1.43 ± 0.3% per year, this trend agreeing with other shortterm regional trends in overall sea ice (pack ice + fast ice) for different sectors of the coast Comiso, 2009). Pezza et al (2012) also report a modest increasing trend in sea-ice area around Antarctica over the era of satellite coverage, as documented by , , , Turner et al (2007), and . Pezza et al's broader study derived a history of Antarctic sea ice for 1979-2008, based upon remotely sensed data from the NASA's Nimbus-7 SMMR and DMSP SSM/I passive microwave satallites.…”
Section: Antarctic Sea Icesupporting
confidence: 73%
“…The ice area study across East Antarctica (10°W to 172°E) revealed a statistically significant increase of 1.43 ± 0.3% per year, this trend agreeing with other shortterm regional trends in overall sea ice (pack ice + fast ice) for different sectors of the coast Comiso, 2009). Pezza et al (2012) also report a modest increasing trend in sea-ice area around Antarctica over the era of satellite coverage, as documented by , , , Turner et al (2007), and . Pezza et al's broader study derived a history of Antarctic sea ice for 1979-2008, based upon remotely sensed data from the NASA's Nimbus-7 SMMR and DMSP SSM/I passive microwave satallites.…”
Section: Antarctic Sea Icesupporting
confidence: 73%
“…Findings of both the present study concerning summer mean daily temperature extremes and the previous study by the same author concerning winter temperatures (Bednorz 2011) correspond to the increase in daily maximum and minimum temperatures in the second half of the twentieth century proved for the Fennoscandia and Nordic Sea regions (Tuomenvirta et al 2000). They also confirm the contemporary warming in the Arctic, widely described in several studies (e.g., Brázdil 1988;Førland et al 1997;Moritz et al 2002;Comiso 2003;Polyakov et al 2003;Przybylak 2000Przybylak , 2002Przybylak , 2003Przybylak , 2007Johannesen et al 2004;Styszyńska 2005;Turner et al 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The rise in the Arctic air temperature in recent decades has exceeded the scale of warming observed in this region in the 1920s and 1930s (Johannessen et al, 2004;Przybylak, 2002Przybylak, , 2007Przybylak, , 2016Turner et al, 2007;Turner and Marshall, 2011). As a result, large changes in environment (e.g.…”
Section: Introductionmentioning
confidence: 99%